Unleash the power of the female brain [compact disc, unabridged] : supercharging yours for better health, energy, mood, focus, and sex - Amen, Daniel G. (Random House Audio, 2013)
From one of the world's leading experts on how the brain works, a step-by-step, practical program for women to achieve greater health, energy, and lasting happiness by harnessing the power of the female brain.